2015
DOI: 10.1164/rccm.201410-1848oc
|View full text |Cite
|
Sign up to set email alerts
|

Improving Selection Criteria for Lung Cancer Screening. The Potential Role of Emphysema

Abstract: LC screening based solely on NLST criteria could miss a significant number of LC cases. Combining NLST criteria and emphysema to select screening candidates results in higher LC detection rates and a lower number of cancers missed.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

5
70
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
4
1
1

Relationship

0
6

Authors

Journals

citations
Cited by 98 publications
(75 citation statements)
references
References 36 publications
5
70
0
Order By: Relevance
“…The authors concluded that the results obtained in the LC screening program were comparable to observations that had been previously reported in other European programs, and that LDCT was a valid and feasible diagnostic tool in this context (3). In another study, the same investigators (4) showed that LC screening programs that are exclusively based on the National Lung Screening Trial (NLST) criteria may fail to identify all the cases of LC. On this basis, the investigators suggested that the application of the NLST criteria in patients with emphysema enhanced the detection rates of LC, while lowered the number of missed cases (4).…”
Section: Evidence and Epidemicssupporting
confidence: 63%
See 4 more Smart Citations
“…The authors concluded that the results obtained in the LC screening program were comparable to observations that had been previously reported in other European programs, and that LDCT was a valid and feasible diagnostic tool in this context (3). In another study, the same investigators (4) showed that LC screening programs that are exclusively based on the National Lung Screening Trial (NLST) criteria may fail to identify all the cases of LC. On this basis, the investigators suggested that the application of the NLST criteria in patients with emphysema enhanced the detection rates of LC, while lowered the number of missed cases (4).…”
Section: Evidence and Epidemicssupporting
confidence: 63%
“…In this regard, low-dose computerized tomography (LDCT) has been proposed as a useful screening tool for LC (85). In keeping with, several authors (3,4,86,87) have demonstrated the benefits of LDCT in the early diagnosis of LC among smokers. Nonetheless, other authors have claimed that in LC screening programs, LDCT should not be still widely applied in the general population up until more convincing results are published (2).…”
Section: Evidence and Epidemicsmentioning
confidence: 99%
See 3 more Smart Citations